Shielding of Photosynthetic Apparatus by Consortia of Bacterial Endophytes in Tomato Plants Suffering From Fusarium Wilt - Chaturvedi, Himani; Singh, Bhupendra; Jajoo, Anjana; Prakash, Anil (Frontiers in Agronomy, 2022)
Fusarium oxysporum is one of the most damaging plant pathogens causing Fusarium wilt in many plants leading to serious economic loss. The fungus colonizes the xylem, which leads to resistance in water flow in the plant thereby affecting the rate of photosynthesis. The present study focuses on the selection of bacterial endophytes isolated from tomato plants and evaluating their potential to antagonize Fusarium oxysporum in tomato in vivo. The results obtained indicated that two endophytic isolates, namely Pseudomonas fluorescens BUMD5 and Bacillus velezensis BUMD9, could act as efficient biocontrol agents (BCAs) as they inhibited the growth of pathogen by 67.2 and 69.1%, respectively, in vitro. Both the isolates were found to produce hydrolytic enzymes chitinase and protease. They also produced siderophore and hydrogen cyanide (HCN). The consortia of both the isolates significantly reduced the infection percentage by about 67% and a 3-fold decrease in disease severity was observed as compared to pathogen control. The treatment of infected plants with these potent isolates was also beneficial in improving the overall photosynthetic performance index (PI). Thus, plants treated with consortia of these isolates exhibited better overall plant growth despite being infected by the pathogen.